(untitled) - Haines, Simon (Oxford, 2008)
A complete preparation course for IELTS offers topic development to encourage students to think critically. A Language for Writing syllabus covers grammar and vocabulary. Help Yourself pages with activities to support self-study are provided.
Keywords: English language,English language,Tiếng Anh; Textbooks for foreign speakers,Examinations, questions, etc.,Giáo trình dành cho người nước ngoài